Dampak Pandemi Covid-19 Terhadap Budaya Sadranan Di Dukuh Prigi Desa Tanduk - Khabib Asnawi; Evi Elisanti; Aris Prio Agus Santoso; Aas Rohmat (Prodi Sosiologi Universitas Mataram, 2022)
The Covid-19 pandemic has changed many sectors of human life, including the impact on the social, cultural, economic and health sectors, an example of the cultural sector is the prohibition of the sadranan tradition. The purpose of this article is to provide an overview to the public how a noble sanctity of culture can become extinct due to the influence of the COVID-19 pandemic. This research method is a literature review approach, with secondary data collection sourced from information, research results and also observations. The results of this study indicate that to anticipate that the sadranan tradition does not become extinct are: Building people's awareness that the sadranan tradition is an ancestral heritage that needs to be preserved. Making the sadranan tradition as a community identity and studying the history of sadranan.